Closing the gap in a generation : health equity through action on the social determinants of health : final report (WHO GenevaCH, 2008)
Sets out key areas - of daily living conditions and of the underlying structural drivers that influence them - in which action is needed. Provides analysis of social determinants of health and concrete examples of action that have proven effective in improving health and health equity in countries at all levels of socioeconomic development.
Keywords: ACCESS TO HEALTH CARE